A Novel Nonsense GLI3 Variant Is Associated With Polydactyly and Syndactyly in a Family by Blocking the Sonic Hedgehog Signaling Pathway - Xiang, Ying; Li, Xiaoliang; Zhan, Zhiyan; Feng, Jue; Cai, Haiqing; Li, Yanxin; Fu, Qihua; Xu, Yunlan; Jiang, Hong; Zhang, Xiaoqing (Frontiers in Genetics, 2020)
Polydactyly and syndactyly are congenital limb malformations that may occur either as non-syndromic or syndromic forms. In the present study, massively parallel sequencing was performed on a proband in a four-generation family with polydactyly and syndactyly to identify disease-causing variant(s). A pathogenic variant c.739C>T (p.Gln247*) in the glioma-associated oncogene family zinc finger 3 (GLI3) gene was identified and co-segregated with the affected members of the family. Firstly, we examined GLI3 mRNA and GLI3 protein levels in peripheral blood mononuclear cells (PBMCs) of patients carrying this variant. The results showed that the truncated GLI3 p.Gln247* (c.739C>T) protein was detectable in patients and the GLI3 transcript and protein levels were not significantly altered in the PBMCs of patients compared with healthy controls. Furthermore, functional analysis showed that the truncated GLI3 p.Gln247* (c.739C>T) protein variant could lead to cytoplasmic accumulation of mutant protein and loss of ability to bind to the Suppressor of Fused protein. Alterations in protein expression levels of core components of the Sonic hedgehog signaling pathway were also observed. Our study shows that this novel GLI3 variant contributes to the malformations in this family and provides evidence for the mechanism by which the GLI3 c.739C>T (p.Gln247*) implicated in the pathogenesis of polydactyly and syndactyly.